Vulnerability Analysis of Interdependent Scale-Free Networks with Complex Coupling. (14th August 2017) - Cao, Chunjie; Zhang, Zhiqiang; Sun, Jingzhang; Wang, Xianpeng; Huang, Mengxing
Abstract : Recent studies have shown that random nodes are vulnerable in interdependent networks with simple coupling. However, relationships in actual networks are interrelated and complex coupling. This paper analyzes the vulnerability of interdependent scale-free networks with complex coupling based on the BA model. The results indicate that these networks have the same vulnerability against the maximum node attack, the load of the maximum node attack, and the random node attack, which explain that the coupling relationship between network nodes is an important factor in network design.